Anti-bacterial and cytotoxic effects of King cobra (Ophiophagus hannah) venom L-amino acid oxidase / Lee Mui Li - Lee, Mui Li (2014)
King cobra (Ophiophagus hannah) venom L-amino acid oxidase (OH-LAAO), a heat stable enzyme, has been shown to exhibit bactericidal activity against several strains of clinical isolates Gram-positive and Gram-negative bacteria. Its potency was compared with some common antibiotics such as cefotaxime, kanamycin, tetracycline, vancomycin and penicillin. King cobra venom LAAO was effective in inhibiting Gram-positive bacteria tested, with minimum inhibitory concentration (MIC) of 0.78 μg/mL (0.006 μM) and 1.56 μg/mL (0.012 μM) against S. aureus and S. epidermidis, respectively. The MICs are comparable to the MICs of the antibiotics tested. However, the OH-LAAO was moderately effective against the Gram-negative bacteria tested (P. aeruginosa, K. pneumonia, and E. coli), with MIC ranges from 25 to 50 μg/mL (0.2 - 0.4 μM). Catalase (1 mg/mL) significantly abolished the bactericidal activity of OH-LAAO, indicating that the antibacterial effect of the enzyme involves generation of hydrogen peroxide. Binding studies indicated that OH-LAAO binds strongly to the Gram-positive S. aureus and S. epidermidis, but less strongly to the Gram-negative E. coli and P. aeruginosa, suggesting that specific binding to the bacteria is important for its potent antibacterial activity. The enzyme was also shown to exhibit very potent anti-proliferative activity against human tumourigenic breast (MCF-7), lung (A549), promyelocytic leukaemia (HL-60) and prostate (PC-3) cells, with IC50 of 0.04 - 0.07 μg/mL after 72 h incubation. In comparison, its cytotoxicity was about 3 to 4 times lower when tested against the non-tumourigenic breast (184B5) and lung (NL 20) cells, suggesting selective anti-tumour activity. Furthermore, its potency in human tumourigenic cells was greater than the effects of doxorubicin, which has an IC50 of 0.1 - 0.63 μg/mL. The selective cytotoxic action of the OH-LAAO was confirmed by PE-annexin V/7-AAD apoptotic assay. The ability of OH-LAAO in inducing apoptosis in tumour cells was further demonstrated using caspase-3/7 and DNA fragmentation assays. Apoptosis induction activity of the enzyme is via both intrinsic and extrinsic pathways as indicated by increase in caspase-9 and -8 activities as well as increased cytochrome c levels in both cytosolic and mitochondria fractions in the LAAO-treated cells. The generation of H2O2 plays a significant role in the cytotoxic action of the enzyme, as its cytotoxicity was significantly reduced in the presence of catalase (a H2O2 scavenger). It was postulated that the alterations of gene and protein expression in cells treated with OH-LAAO, as observed in microarray and proteomics studies, were largely caused by non-specific oxidative modifications of signalling molecules that eventually lead to apoptosis and cell death. Administration of 1 μg/g (i.p.) of OH-LAAO to PC-3 tumour-bearing NU/NU mice markedly inhibited the tumour growth. TUNEL staining analysis on the tumour sections showed a significantly increase of apoptotic cells in the LAAO-treated animals. The enzyme also did not cause any significant pathology changes on the vital organs as well as the body weight of the treated mice. In view of its heat stability, its selective and potent cytotoxic action on cancer cells, OH-LAAO can be potentially developed for treating solid tumours.